GOODWILL HUNTING - Napitupulu, Daniel (UI Scholars Hub, 2004)
We have not yet had high quality international standards which can be used all over the world. Thus, we need to work together to make such things. An important standard that need to be done is the one about goodwill recognition. US GAAP, UK GAAP and International Accounting Standard give different guidance. Harmonization of these standards will create a uniformed goodwill accounting which consistently can be applied by companies.